Assessing cognitive performance in nature: brain size and personality correlates of novel object recognition in nest-guarding male pumpkinseed sunfish - McAllister, Keith; Dolan, Maria; Axelrod, Caleb J.; Robinson, Beren W.; Laberge, Frédéric (Frontiers in Ethology, 2025)
Studying the factors that determine cognitive performance in animals is challenging under natural conditions but necessary to ensure that the laboratory test results are relevant to wild populations. We took advantage of nest fidelity in parental male pumpkinseed sunfish (Lepomis gibbosus) to conduct a novel object recognition (NOR) assay in the field. We assessed consistent individual differences in behaviour across the object familiarisation and test phases of the NOR assay and collected anatomical measurements, including brain size, after assay completion. We hypothesised that brain size would influence pumpkinseed cognitive ability and predict NOR performance after accounting for individual behavioural differences. Parental males showed repeatable reactions to nest disturbance and to the presence of objects at the nest periphery between assay phases, as well as correlated object investigation behaviours. We found evidence of novel object recognition memory at the population level, although it varied widely among individuals. Individual differences in object interactivity did not influence NOR performance, but relative brain mass (corrected for body length) did. Parental male pumpkinseed with relatively larger brains performed more poorly than males with relatively smaller brains. We interpret this negative relationship between brain size and NOR performance in the context of severe energy limitations faced by parental males during reproduction. Specifically, males maintaining energetically costly larger brains are likely operating near their upper energetic limit, with little or no spare resources available for investment in demanding learning processes. If this is the case, our findings emphasise that relationships between brain size and cognitive test performance may depend on energy availability and expenditure rates.